(untitled) (Boston, 2001)
This volume gathers together a representative set of examples from the many varied spatial techniques and analytical approaches being used by geographers, ecologists, and biogeographers to study plant and animal distributions, to assess processes affecting the observed patterns at selected spatial and temporal scales, and to discuss these examples within a strong conceptual spatial and/or temporal framework.
Keywords: Biogeography,Ecology,Geographic information systems,Sinh thái học,Hệ thống thông tin địa lý; Remote sensing,Remote sensing,Địa lý sinh vật; Địa lý sinh vật